Peningkatan Profitabilitas Serta Pengaruh Dana Syirkah Temporer, Kewajiban dan Ekuitas dengan Variabel Risiko Pembiayaan Sebagai Antiseden (Studi pada Perbankan Syariah di Indonesia) - Marheni, Marheni (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2016)
The purpose of this study is the effect of temporary syirkah funds, liabilities and equity of the financing risk and profitability of Islamic banks in Indonesia; analysis of effect financing risk on profitability. The population is Islamic bank in Indonesia. The sample was selected using purposive sampling method. Observation number 11 bank research. Method of data analysis used the path analysis. Results of this study indicate that the fund temporary syirkah positive significant effect on the risk of financing received. The more the amount of funds held temporary syirkah the risk of non-performing loans to finance or Islamic banks NPF indicator becomes smaller. Obligations positive significant effect on the risk of financing. The larger a bank's liabilities, the risk of non-performing loans to the financing or NPF indicator will also be greater. no significant effect on the risk of financing. This means that the level of equity had no impact on the level of financing risk. Fund temporary syirkah positive significant effect on profitability. Obligations positive significant effect on profitability. Debt obligations or received will indirectly increase the amount of income. Equity does not significantly influence the risk of financing. This means that the size of the equity has no effect on the level of profitability and ROA indicators received by commercial banks financing syariah.Risiko significant negative effect on profitability. Conclusion the study shows that the temporary syirkah funds and liabilities have a significant effect on the risk of equity financing and profitability while no significant effect on risk financing and profitability.